Citra Merek, Harga, Dan Kepercayaan Sebagai Prediktor Niat Pembelian Tiket Melalui Platform Digital - Rusdiansyah, Rusdiansyah; Syahran, Syahran; Sugiati, Tinik; Karunia , Erick; Ardiansyah, Riyans (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
Abstract This study aims to analyze the influence of brand image, price, and trust on consumers’ intention to purchase tickets online. A quantitative approach with SEM-PLS was employed, involving 280 respondents in Tarakan City selected through purposive sampling. Data were collected using a seven-point Likert scale questionnaire and analyzed with SmartPLS 3.0. The results show that brand image significantly affects both price perception and consumer trust. Furthermore, price and trust were found to positively influence online purchase intention. Thus, brand image not only shapes consumers’ perception of price but also enhances their level of trust. At the same time, strong trust and reasonable pricing encourage consumers to proceed with purchasing decisions. These findings highlight that brand image and trust are essential elements in marketing strategies for online ticket providers, helping to attract consumers and strengthen their intention to buy. Keywords: Brand image, Price, Trust, Purchase intention, Online ticket, SEM-PLS